Analisis Kinerja Sistem Transmisi Hidrolik pada Prototipe Excavator Model Crawler - Dewi Nursari; Sriyono; Tatang Permana (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
The hydraulic transmission system is a key component of an excavator because it transfers fluid power from the pump to the actuators to produce working movements of the boom, arm, and bucket. This study aims to analyze the performance of the hydraulic transmission system in a crawler-type miniature excavator prototype based on working load, cylinder cross-sectional area, working pressure, cylinder speed, flow rate, and pump requirement. The research used a Research and Development (R&D) method with limited stages of define, design, development, and disseminate. The prototype was designed using CAD software, manufactured through 3D printing with PLA+ material, and equipped with a simple hydraulic system to operate the boom, arm, and bucket cylinders. The analysis was conducted by determining load distribution based on the center of gravity, calculating the force acting on each cylinder, and determining the cylinder area, working pressure, and actuator flow rate. The results showed that the boom cylinder received the highest load of 20 kg, while the arm and bucket cylinders received 10 kg and 5 kg, respectively. The boom cylinder area was 0.000314 m², while the arm and bucket cylinder areas were 0.000491 m². The required working pressures for the boom, arm, and bucket cylinders were 72 bar, 30 bar, and 20 bar, with flow rates of 0.565 lpm, 1.470 lpm, and 2.063 lpm, respectively. These results indicate that the boom cylinder is the most critical component based on pressure requirement, while the bucket cylinder determines the highest flow demand. Therefore, pump selection should consider a maximum pressure of 72 bar and a minimum flow rate of 2.063 lpm, with additional flow capacity when multiple actuators operate simultaneously.